Arithmetic Progression
Question 2
Question 3 Important
Question 4
Question 5 Important
Question 6
Question 7 Important
Question 8
Question 9 Important
Question 10
Question 11 Important
Question 12
Question 13
Question 14 Important
Question 15 Important You are here
Question 16 Important
Question 17
Question 18 Important
Arithmetic Progression
Last updated at April 16, 2024 by Teachoo
Ex 9.2 , 15 If (𝑎^𝑛 + 𝑏^𝑛)/(𝑎^(𝑛−1) + 𝑏^(𝑛−1) ) is the A.M. between a and b, then find the value of n. We know that arithmetic mean between a & b is A.M. = (a + b)/2 It is given that AM between a & b is (𝑎^𝑛 + 𝑏^𝑛)/(𝑎^(𝑛−1) + 𝑏^(𝑛−1) ) So, (𝑎^𝑛 + 𝑏^𝑛)/(𝑎^(𝑛−1) + 𝑏^(𝑛−1) ) = (a + b)/2 2(an + bn) = (a + b) (an – 1 + bn – 1) 2an + 2bn = a(an – 1 + bn – 1) + b(an – 1 + bn – 1) 2an + 2bn = aan – 1 + abn – 1 + ban – 1 + bbn – 1 2an + 2bn = a1 . an – 1 + abn – 1 + ban – 1 + b1 . bn – 1 2an + 2bn = a1 + n – 1 + abn – 1 + ban – 1 + b1 + n – 1 2an + 2bn = a1 + n – 1 + abn – 1 + ban – 1 + b1 + n – 1 2an + 2bn = an + abn – 1 + ban – 1 + bn 2an + 2bn – an – abn – 1 – an – 1 b – bn = 0 2an – an + 2bn – bn - abn – 1 – an - 1 b = 0 an + bn – abn – 1 – an – 1 b = 0 an – an – 1 b + bn – a bn – 1 = 0 a.an – 1 – an – 1 b + b.bn – 1 – a bn – 1 = 0 an – 1 (a – b) – bn – 1 (a – b) = 0 (an – 1 – bn – 1)(a – b) = 0 ∴ an – 1 – bn – 1 = 0 Solving an – 1 = bn – 1 an – 1 = bn – 1 𝑎^(𝑛 −1)/(𝑏^(𝑛 −1) ) = 1 (𝑎/𝑏)^(𝑛 −1) = 1 (𝑎/𝑏)^(𝑛 −1) = (𝑎/𝑏)^0 Comparing powers n – 1 = 0 n = 1 Hence n = 1